Emerging importance of satellite glia in nervous system function and dysfunction - Hanani, Menachem (Nat Rev Neurosci, 2020)
Satellite glial cells (SGCs) closely envelop cell bodies of neurons in sensory, sympathetic and parasympathetic ganglia. This unique organization is not found elsewhere in the nervous system. SGCs in sensory ganglia are activated by numerous types of nerve injury and inflammation. The activation includes upregulation of glial fibrillary acidic protein, stronger gap junction-mediated SGC–SGC and neuron–SGC coupling, increased sensitivity to ATP, downregulation of Kir4.1 potassium channels and increased cytokine synthesis and release. There is evidence that these changes in SGCs contribute to chronic pain by augmenting neuronal activity and that these changes are consistent in various rodent pain models and likely also in human pain. Therefore, understanding these changes and the resulting abnormal interactions of SGCs with sensory neurons could provide a mechanistic approach that might be exploited therapeutically in alleviation and prevention of pain. We describe how SGCs are altered in rodent models of four common types of pain: systemic inflammation (sickness behaviour), post-surgical pain, diabetic neuropathic pain and post-herpetic pain.